The perverse impact of external reference pricing (ERP): a comparison of orphan drugs affordability in 12 European countries. A call for policy change - K. E. Young; I. Soussi; M. Toumi (Journal of Market Access & Health Policy, 2017)
Objective: The study compared the relative cost differences of similar orphan drugs among high and low GDP countries in Europe: Bulgaria, France, Germany, Greece, Hungary, Italy, Norway, Poland, Romania, Spain, Sweden, UK. Methods: Annual treatment costs per patient were calculated. Relative costs were computed by dividing the costs by each economic parameter: nominal GDP per capita, GDP in PPP per capita, % GDP contributed by the government, government budget per inhabitant, % GDP spent on healthcare, % GDP spent on pharmaceuticals, and average annual salary. An international comparison of the relative costs was done using UK as the reference country and results were analysed descriptively. Results: 120 orphan drugs were included. The median annual costs of orphan drugs in all countries varied minimally (cost ratios: 0.87 to 1.08). When the costs were adjusted using GDP per capita, the EU-5 and Nordic countries maintained minimal difference in median cost. However, the lower GDP countries showed three to six times higher relative costs. The same pattern was evident when costs were adjusted using the other economic parameters. Conclusion: When the country’s ability to pay is taken into consideration, lower GDP countries pay relatively higher costs for similarly available orphan drugs in Europe.